Histopathological Description of Mouse Liver in a Sepsis Model Infected with Escherichia coli Treated with Paederia foetida L. Leaf Extract for Sepsis Prevention - Savitri, Lisa; Retnowati, Ana; Kasimo, Elfred Rinaldo; Krissanjaya, Rochmad; Juwita, Syntia Tanu (Biology, Medicine, & Natural Product Chemistry, 2024)
The leaf of Paederia foetida L. is one type of medicinal plant that can be used as a preventive medicine for sepsis. This plant contains secondary metabolites such as alkaloids, flavonoids, triterpenoids, saponins, and other active compounds. The objective of this study was to determine the histopathological description of the liver in a mouse sepsis model infected with E. coli, with the administration of Paederia foetida L. leaf extract for sepsis prevention, and to ascertain the influence and effective dosage of the leaf extract as a preventive measure against liver histopathology in the sepsis model induced by E. coli. The method employed was a Completely Randomized Design (CRD). The study used 24 male white mice divided into 6 (six) groups. Data analysis was conducted using One Way ANOVA. The results of the study revealed the histopathological profile of liver cell degeneration in group PI (100mg/kg BW) at 20.79%±0.03, group PII (200mg/kg BW) at 21.63%±0.02, and group PIII (500mg/kg BW) at 9.08%±0.02. Necrosis rates were observed in group PI (100mg/kgBW) at 22.62%±0.04, group PII (200mg/kg BW) at 17.63%±0.02, and group PIII (500mg/kg BW) at 6.05%±0.02. The presence of polymorphonuclear leukocytes (PMN) was detected in group PI (100mg/kgBW) at 39.56%±0.03, group PII (200mg/kgBW) at 28.05%±0.02, and group PIII (500mg/kg BW) at 18.45%±0.03. The test results showed a significant effect of P. foetida L. leaf extract as a preventive measure against liver histopathology in the mouse sepsis model infected with E. coli, with significant values for necrosis (p=0.000), cell degeneration (p=0.000), and PMN (p=0.000). The most effective dosage of P. foetida L. leaf extract as a preventive measure against liver histopathology in the mouse sepsis model infected with E. coli was the dosage used in group PIII (500mg/kgBW).